Pride and Prejudice - Austen, Jane (New York Penguin Books, 1994)
In Pride and Prejudice, the Bennet sisters try to find their way in the repressive strictures of 19th century society. Austen shows the folly of judging by first impressions and the experience of falling in love, and she superbly describes a world which, despite being more than two centuries old, still resonates with modern concerns.